2018
DOI: 10.3390/su10061730
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey Evaluating the Environmental Literacy of Undergraduate Students in Taiwan

Abstract: The aim of this nationwide survey was to assess undergraduate students' environmental literacy level in Taiwan. A total of 29,498 valid responses were received from a number of selected colleges and universities in Taiwan, using stratified random sampling method. A total of 70 items were used to assess the environmental literacy and the results revealed that undergraduate students had a relatively low level of environmental knowledge and behavior, while a moderate level of environmental attitudes was attained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 55 publications
6
62
0
6
Order By: Relevance
“…This pattern is generally in line with the findings by Fang et al (2018), which indicated higher means among Taiwanese female university students for knowledge, attitudes and behavior intention within the environmental dimension. This has also been confirmed for Taiwanese undergraduate students (Liang et al 2018). Our results indicated stronger knowingness among males than females in the Taiwanese sample, which contradicts the findings by Fang et al and Liang et al However, it should be noted that our construct of sustainability knowingness reflects an awareness of the theoretical components of SD rather than factual knowledge about environmental, social and economic issues.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…This pattern is generally in line with the findings by Fang et al (2018), which indicated higher means among Taiwanese female university students for knowledge, attitudes and behavior intention within the environmental dimension. This has also been confirmed for Taiwanese undergraduate students (Liang et al 2018). Our results indicated stronger knowingness among males than females in the Taiwanese sample, which contradicts the findings by Fang et al and Liang et al However, it should be noted that our construct of sustainability knowingness reflects an awareness of the theoretical components of SD rather than factual knowledge about environmental, social and economic issues.…”
Section: Discussionsupporting
confidence: 56%
“…The mean difference between the Taiwanese and Swedish samples for sustainability behaviors is close to 0.7, a substantial difference on a scale ranging between 1 and 5, for which most responses are found within a smaller part of the scale (the upper half). The stronger knowingness and attitudes and weaker behaviors for the Swedish students compared to Taiwanese students give further support for the criticism of simplistic interpretations concerning causal relationships between knowledge, attitudes and behaviors (e.g., Kollmuss and Agyeman 2002;Booth 2009;Michalos et al 2012;Fang et al 2018;Liang et al 2018).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The research results by Ozgurler & Cansaran (2014), environmental knowledge of graduate students is not at a high level, but their approach to literacy ecology problem is at a high level. Liang et al (2018) explained that attitudes, knowledge, and behavior of women have better environmental concerns than men in higher education. However, Hammarsten et al 2018and Jannah et al (2013) showed that the development of environmental literacy for students could have practical impacts including competence, caring learning, and understanding of ecological knowledge.…”
Section: Introductionmentioning
confidence: 99%